2015
DOI: 10.1177/016146811511700108
|View full text |Cite
|
Sign up to set email alerts
|

Reading Attitude as a Mediator between Contextual Factors and Reading Behavior

Abstract: Background Among the factors known to influence reading development and performance, attitude toward reading is shown to be particularly critical for developing learners. Reading attitude enhances independent reading, levels of engagement in classroom reading activities, and the amount and variety of topics in reading, which in turn influence reading skills and strategies. Reading attitude is an important element in students’ active engagement and achievement in reading. Purpose The first purpose of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
4
7
1
1
Order By: Relevance
“…From one perspective, this accords with earlier observations that demonstrate solid while positive prediction of reading attitudes to reading achievement (Logan & Johnston, 2009;Martinez et al, 2008;Sainsbury & Schagen, 2004). This outcome is also in line with Lim et al (2015), who stated that reading attitudes were predominantly vital for developing reading literacy. From another perspective, this finding is contrary to previous studies which suggest that there exist negative associations between reading attitudes and reading performance (Kush & Watkins, 1996;Martinez et al, 2008;McKenna et al, 2012;McKenna et al, 1995;Sölpük, 2017).…”
Section: Factor Structure Of Digital Reading Achievementsupporting
confidence: 90%
See 3 more Smart Citations
“…From one perspective, this accords with earlier observations that demonstrate solid while positive prediction of reading attitudes to reading achievement (Logan & Johnston, 2009;Martinez et al, 2008;Sainsbury & Schagen, 2004). This outcome is also in line with Lim et al (2015), who stated that reading attitudes were predominantly vital for developing reading literacy. From another perspective, this finding is contrary to previous studies which suggest that there exist negative associations between reading attitudes and reading performance (Kush & Watkins, 1996;Martinez et al, 2008;McKenna et al, 2012;McKenna et al, 1995;Sölpük, 2017).…”
Section: Factor Structure Of Digital Reading Achievementsupporting
confidence: 90%
“…Attitudes towards reading are known to be one of the most critical factors that influence reading performance and achievement (Lim et al, 2015). Swalander and Taube (2007) defined reading attitude as one's un/favorable disposition towards reading.…”
Section: Reading Attitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…With the same objective as Lim et al (2015), researchers from the Chilean Agency of Educational Quality (CAEQ) developed a multilevel model to examine how demographic variables, SES factors, literacy-related habits, teacher practices, and school characteristics contributed to predicting Chilean tenth graders' reading motivation (Agencia de Calidad de la Educación, 2016). Using the 2015 national reading assessment data set (SIMCE; System of Measurement of Educational Quality, acronym in Spanish) they found that, while controlling for other variables, parents' self-reported reading motivation level was a significant predictor of students' reading motivation.…”
Section: Parents' Beliefs and Motivationmentioning
confidence: 99%